Stretchable and semitransparent conductive hybrid hydrogels for flexible supercapacitors - Hao, Guang-Ping; Hippauf, Felix; Oschatz, Martin; Wisser, Florian M.; Leifert, Annika; Nickel, Winfried; Mohamed-Noriega, Nasser; Zheng, Zhikun; Kaskel, Stefan (ACS nano, 2014)
Conductive polymers showing stretchable and transparent properties have received extensive attention due to their enormous potential in flexible electronic devices. Here, we demonstrate a facile and smart strategy for the preparation of structurally stretchable, electrically conductive, and optically semitransparent polyaniline-containing hybrid hydrogel networks as electrode, which show high-performances in supercapacitor application. Remarkably, the stability can extend up to 35 000 cycles at a high current density of 8 A/g, because of the combined structural advantages in terms of flexible polymer chains, highly interconnected pores, and excellent contact between the host and guest functional polymer phase. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: conductive polymer; flexible supercapacitor; long cycling stability; polyaniline; stretchable and transparent hydrogel